Training Critical Thinking Professionals Through İmece Circles and Concept Maps - Hayal Köksal (Üniversite Araştırmaları Dergisi)
Education starts in family and goes on under the guidance ofschool professionals, teachers. Learning, which isthe goal of schooling, is a complex process. It can only be effective throughqualified teachers who are aware of the significance of knowing and applyingrecent cognitive methodologies such as concept maps. Concept maps are a way todevelop critical and logical thinking study skills by revealing connections andhelping students see how individual ideas form a larger whole. As is known bymany, meaningful learning involves the assimilation of new concepts andpropositions into existing cognitive structures. Professionals, as the leadingforces of future leaders, need to be trained basedupon the satisfaction of above-mentioned needs during the university years. Inthis article, the author will share the goals, steps and outcomes of two “Concept-Mapping”workshops conducted at “Classroom management” course at a Faculty of Education.The readers will also find reflections of the teacher-trainees impressive.